Low-cost portable potentiostat for real-time insulin concentration estimation based on electrochemical sensors - Dewi, Fitria Yunita; Aliwarga, Harry Kusuma; Handoko, Djati (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Administering incorrect insulin dosages to diabetic patients can be fatal, leading to severe health consequences. Insulin detection, in conjunction with blood glucose monitoring, can significantly enhance diagnostic accuracy. Electrochemical methods for insulin detection offer a low-cost and portable solution. This study presents an insulin concentration estimation system using a customized electrochemical potentiostat operating in real-time via Bluetooth low energy (BLE). Conventional electrochemical sensing, which relies on calibration curves to determine concentration, poses accuracy limitations in portable devices. To address this, we implement a multiple- predictor approach that incorporates peak currents from multiple cycles of cyclic voltammetry responses and the electroactive surface area of a multi- walled carbon nanotube (MWCNT-COOH) modified screen-printed sensor. This modified sensor enhances sensitivity compared to bare screen-printed carbon sensors, making it suitable for low-volume and portable applications. Through cross-validation, our method demonstrated strong performance, achieving a determination coefficient (R²) greater than 0.90 for all training dataset combinations and greater than 0.85 for all testing dataset combinations. Hypothesis testing further confirmed the statistical significance of the electroactive surface area (p=0.006) as predictor, indicating its meaningful contribution to concentration estimation. This approach improves portable detection performance, supporting the development of affordable and reliable personal insulin monitoring systems.